DETERMINANTS OF CONSUMER PURCHASE DECISIONS IN THE AGROINDUSTRY OF ECO-ENZYME SOAP FOR WOVEN TEXTILES AT CV. MAZMUR ECO SHOP IN KUPANG CITY - Palastri, Azalia Anindya; Pellokila, Marthen Robinson; Darlen, Maria Fransisca (Buletin Ilmiah Impas, 2025)
The issue of organic waste management remains a serious environmental challenge in Indonesia. Eco-enzyme has emerged as one potential solution for organic waste management because it can be used as a raw material for organic soap that is environmentally friendly and has practical value. This study aims to analyze the determining factors of consumer purchasing decisions for eco-enzyme soap for woven textiles at CV. Mazmur Eco Shop, Kupang City. The study employed a quantitative approach using binary logistic regression with 100 respondents selected through purposive sampling. The results show that price and consumer trust have a significant effect on purchasing decisions, whereas perceived product quality is not significant. These findings indicate the importance of pricing strategies and consumer education in increasing consumer trust and encouraging the purchase of eco-enzyme soap.